Perubahan Sosial Masyarakat Desa Raya Kab Simalungun - Adinda Kartika Sari (Yayasan Azzuhri Lengkok Lombok Timur, 2023)
Changes in society can be about social values, social norms, patterns of organizational behavior, the composition of social institutions, layers in society, power and authority, social interactions and so on. Nearly 80% or more of Indonesia's population live in rural areas. Thus, rural areas are not only a source of economic strength. Based on the paper above, a paper was created entitled